The Treason of The Intellectuals an Essay About the Hungarian Lesson - Szélinger, Balázs (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
As the subtitle indicates, this is not a scholarly article based on research but one almost identical to the oral presentation I gave during the workshop “30 Years of Freedom – Farewell to Communism in Hungary, Local and Global Lessons” in Addis Ababa on October 25, 2019, organized jointly by the Embassy of Hungary in Addis Ababa, the Ethiopian Civil Service University, the Hungarian National University of Public Service, and the University of Pécs, Hungary. I made every effort to strengthen my arguments with valuable references.